The Role of Thrombin in Fibrinogen Biosynthesis - Pickart, L. R; Pilgeram, L. O (Thrombosis and Haemostasis, 1967)
Mouse liver slices incubated in a human serum medium displayed significantly greater incorporation of glycine-14C into fibrinogen than when incubated with plasma. Preincubation of heat defibrinated plasma with thrombin produced an increase in the level of biosynthesis comparable to that induced by serum whereas defibrination of the plasma incubation medium exerted no stimulatory effect on biosynthesis. Subcutaneous injection of 50 u of heterologous thrombin into Swiss albino mice induced an increase (0.5 to 1.9 fold) in the rate of biosynthesis of fibrinogen comparable to that induced in vitro by blood derived from aging or arteriosclerotic human subjects. Thrombin is not the primary agent in the control of the synthesis of fibrinogen since the activity of thrombin, when preincubated with plasma, had disappeared before the plasma was used as a medium for stimulating the synthesis of fibrinogen. Also, incubation of serum led to the production of a factor which greatly enhanced the biosynthesis of fibrinogen. This condition is not known to lead to the production of thrombin.